Sosialisasi Penataan Ruang dalam Mendukung Sistem Transportasi Multimoda Sulawesi Selatan - Natalia, Venny Veronica; Mandasari, Jayanti; Abduh, Andi Munawarah; Patandianan, Marly Valenti; Rasyid, Abdul Rachman; Nur, Dewi Sagita Alfadin; Wunas, Shirly; Sutopo, Yashinta Kumala Dewi (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
The transportation system and land use have a reciprocal relationship. Therefore, the construction of the Trans Sulawesi railway will significantly impact the surrounding land use. Additionally, the introduction of rail-based alternative transportation modes will inevitably influence future demand for the movement of people and goods. Therefore, coordination among various stakeholders is essential to integrate rail-based transportation services and development with spatial planning. The objective of this activity is to conduct outreach to policymakers and implementers to integrate the rail-based transportation system with spatial planning. The research method employed involves participatory socialization and discussions with relevant stakeholders. The output of this activity shows an increase in stakeholder understanding and awareness of the importance of integration between transportation systems and land use. The increase in the number of participants who understand the importance of spatial planning in supporting the South Sulawesi multimodal transportation system increased from 77.52% to 91% after the socialization.